Clinical outcomes of vitamin D deficiency and supplementation in cancer patients. (15th August 2013) - Teleni, Laisa; Baker, Jacqueline; Koczwara, Bogda; Kimlin, Michael G; Walpole, Euan; Tsai, Kathy; Isenring, Elizabeth A
Abstract : Results of recent studies suggest that circulating levels of vitamin D may play an important role in cancer‐specific outcomes. The present systematic review was undertaken to determine the prevalence of vitamin D deficiency ( < 25 nmol/L) and insufficiency (25–50 nmol/L) in cancer patients and to evaluate the association between circulating calcidiol (the indicator of vitamin D status) and clinical outcomes. A systematic search of original, peer‐reviewed studies on calcidiol at cancer diagnosis, and throughout treatment and survival, was conducted yielding 4, 706 studies. A total of 37 studies met the inclusion criteria for this review. Reported mean blood calcidiol levels ranged from 24.7 to 87.4 nmol/L, with up to 31% of patients identified as deficient and 67% as insufficient. The efficacy of cholecalciferol supplementation for raising the concentration of circulating calcidiol is unclear; standard supplement regimens of < 1, 000 IU D3 /day may not be sufficient to maintain adequate concentrations or prevent decreasing calcidiol. Dose‐response studies linking vitamin D status to musculoskeletal and survival outcomes in cancer patients are lacking.